Fish fauna composition of Batang Kayan and its tributaries, Lundu, Sarawak - Timothy, Henry Lansing (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study was done to document the fish fauna composition of Batang Kayan and its tributaries. The study was carried out at five selected stations located at the mouth of five tributaries of Batang Kayan namely Sungai Tangilang, Sungai Stenggang, Sungai Bawang, Sungai Tong Senggi and Sungai Stom Lundu. Sampling method used was gill nets of various mesh sizes and three layer gill nets. A total of 324 individuals of fish were caught comprising of 25 species, 17 genera, and 8 families. Among the 8 families, the most dominant family is Cyprinidae. The most dominant species is Chela laubuca with a total of 57 individuals. Four species are present at all stations namely Hemibagrus nemurus, Chela laubuca, Hampala macrolepidota, and Osteochilus waandersii. The station with the largest number of individuals caught is from station 4 with a total of 87 individuals meanwhile the station with lowest number caught is at station 2 with a total of 47 individuals. Species diversity and richness is highest at station 1 which is located at the most upstream of the study site with a value of 1.038 and 7.860 respectively. The fish fauna composition is mainly affected by the habitat characteristics of the river.